2020
DOI: 10.1371/journal.pgen.1008838
|View full text |Cite
|
Sign up to set email alerts
|

ROS regulation of RAS and vulva development in Caenorhabditis elegans

Abstract: Reactive oxygen species (ROS) are signalling molecules whose study in intact organisms has been hampered by their potential toxicity. This has prevented a full understanding of their role in organismal processes such as development, aging and disease. In Caenorhabditis elegans, the development of the vulva is regulated by a signalling cascade that includes LET-60ras (homologue of mammalian Ras), MPK-1 (ERK1/2) and LIN-1 (an ETS transcription factor). We show that both mitochondrial and cytoplasmic ROS act on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 86 publications
0
13
0
Order By: Relevance
“…Using CRISPR/Cas9, we mutated the redox-sensitive Cys366 to serine (Ser), a non-oxidizable Cys mimetic 30 and found no overt phenotypes (Fig. 6 , Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using CRISPR/Cas9, we mutated the redox-sensitive Cys366 to serine (Ser), a non-oxidizable Cys mimetic 30 and found no overt phenotypes (Fig. 6 , Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid damage from H 2 O 2 , C. elegans rely on conserved cellular defenses, including H 2 O 2 -degrading catalases (Chavez et al, 2007; Schiffer et al, 2020). However, inducing those defenses at inappropriate times can cause undesirable side effects, including developmental defects (Doonan et al, 2008; Kramer-Drauberg et al, 2020), because H 2 O 2 modulates the function of proteins involved in a wide variety of cellular processes, including signal transduction and differentiation (Hourihan et al, 2016; Kramer-Drauberg et al ., 2020; Meng et al, 2021; Veal et al, 2007). We recently found that ten classes of sensory neurons in the nematode’s brain manage the challenge of deciding when the nematode’s tissues induce H 2 O 2 defenses (Schiffer et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…1) 1 . These reversible, regulatory oxiPTMs on specific cysteines have emerged as important mechanisms that alter protein function posttranslationally 1,2,6,[10][11][12] .…”
mentioning
confidence: 99%